Energy saving integrated meeting room system with enhanced security features / Vanisa Mayang Jude - Jude, Vanisa Mayang (2024)
In modern office environments, the challenges of inadequate security measures and energy efficiency has risen as a significant concern particularly in meeting rooms. The optimization of energy usage is weakened as these spaces still utilize old technologies in handling the meeting spaces, leading to the escalation of the operational cost and environmental impact. This project addresses the urgency for an integrated system in meeting spaces that balances out energy consumption with prominent security features. This project bridges the gap by introducing an integrated system that would tackles both concerns of energy conservation and security concerns in office meeting rooms. This system utilizes an ultrasonic sensor which aids the system in automatically adjusting the lighting based on room occupancy. The system security is address through a multi-layered approach with combination of a 4x4 matrix keypad, RFID cards, and the Blynk app which controls an electromagnetic lock for the access to the meeting room. This system also provides immediate audio-visual feedback via the buzzer and Light Emitting Diode (LED) as indicators for the successful or unsuccessful access attempts of entry. This system has effectively repelled unauthorized entry attempts which proven the reliability of the system in various security scenarios. This intelligent approach showcases that the integrated system could lead to more secure, efficient, and a sustainable environment by ensuring less energy consumption occurred when the room is unoccupied and provides a user-friendly interface for users while enhancing the room’s security.